PHONOLOGICAL PROCESS OF PREFIX /IN-/ IN FRENCH - Siti Ayu Masthuroh; M Suryadi; Agus Subiyanto (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This article aims to know sound variations of prefix /in-/ in French and to explain phonological process of prefix /in-/ in French. The addition of the prefix / in- / can change the meaning of words into the opposite meaning. This prefix has orthographic and phonetic variation which means there are phonological rules in it, the focus of research is on sound variations and phonological rules prefix / in- / in French. The research subject is French, while the object research is adjective in French with prefix / in- /. This research is a qualitative descriptive study with observation method and note-taking technique. The approach used is transformational generative phonology. The addition of the prefix /in-/ indicates that this prefix has a function as a negative marker (negative prefixes). The result of the analysis shows that sound variations of prefix /in-/ in French are [iŋ-], [in-], [im-], [il-], [iʁ-]. The phonological process that occurs in it is an assimilation process. Assimilation process that occurs in the form of nasalization because there are changes in the sound of consonants that are nasalized in the nasal sound environment.